The Fundamentals of Atomic and Molecular Physics - Brooks, Robert L.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The Fundamentals of Atomic and Molecular Physics is intended as an introduction to the field for advanced undergraduates who have taken quantum mechanics. Each chapter builds upon the previous, using the same tools and methods throughout. As the students progress through the book, their ability to use these tools will steadily increase, along with their confidence in their efficacy. The book treats the two-electron atom as the simplest example of the many-electron atom$1 (Bas opposed to using techniques that are not applicable to many-electron atoms$1 (Bso that it is unnecessary to develop additional equations when turning to multielectron atoms, such as carbon. External fields are treated using both perturbation theory and direct diagonalization and spontaneous emission is developed from first principles. Only diatomic molecules are considered with the hydrogen molecular ion and neutral molecule treated in some detail. This comprehensive coverage of the quantum mechanics of complex atoms and simple diatomic molecules, developed from the very basic components, is extremely useful for students considering graduate studies in any area of physics.s
Part I: Atoms -- Central Forces and Angular Momentum -- Complex Atoms -- Electro- and Magnetostatic Interactions -- Transition Probabilities -- Part II: Molecules -- Electronic Structure of Diatomic Molecules -- Vibrations and Rotations of Diatomic Molecules -- Appendix A. Some Atomic Constants -- Appendix B. Polynomials and Spherical Harmonics -- Appendix C. Some Tensor Background -- Appendix D. Magnetic Dipole Interaction Energy.
Keywords: Physics; Chemistry; Mathematical physics; Physics; Atomic, Molecular, Optical and Plasma Physics; Mathematical Methods in Physics; Theoretical and Computational Chemistry